MODEL OF SWIMMING GAMES TO REDUCE STRESS EXERCISE FOR 12 – 14 YEAR OLDS - Mardinasyan, Eryan; Tahki, Kurnia (Journal of Sport Science and Tourism Activity (JOSITA), 2022)
This study aims to create a swimming game model to reduce exercise stress in children aged 12-14 years, where the researchers are in the area of the Pyramid Swiming Club Bogor, Secretariat: Jl. Raya Cikaret housing Nirwana Estate Cibinong, Bogor Regency. The research time is July 2022. This research method uses the ADDIE research method, where the research uses 5 stages, namely, analysis, design, model development, implementation, evaluation. The results of the study resulted in a product in the form of a swimming game model that had been revised by game experts and swiming experts as many as 7 models which were implemented by 10 people. Based on the results of the study showed that the swimming game model to reduce stress in children aged 12-14 years can be a medium to be used in the swimming training process, especially to reduce exercise stress, so that it can make a good contribution to the coach and children, based on the results of the study. a swimming game model to reduce exercise stress in children 12-14 years old can be developed and can be applied to children.